Higher Expression of Toll-like Receptors 3, 7, 8, and 9 in Pityriasis Rosea - Mostafa Abou El-Ela; Mohamed El-Komy; Rania Abdel Hay; Rehab Hegazy; Amin Sharobim; Laila Rashed; Khalda Amr (Korean Society of Pathologists & the Korean Society for Cytopathology, 2017)
Background Pityriasis rosea (PR) is a common papulosquamous skin disease in which an infective agent may be implicated. Toll-like receptors (TLRs) play an important role in immune responses and in the pathophysiology of inflammatory skin diseases. Our aim was to determine the possible roles of TLRs 3, 7, 8, and 9 in the pathogenesis of PR. Methods Twenty-four PR patients and 24 healthy individuals (as controls) were included in this case control study. All recruits were subjected to routine laboratory investigations. Biopsies were obtained from one active PR lesion and from healthy skin of controls for the detection of TLR 3, 7, 8, and 9 gene expression using real-time polymerase chain reaction. Results This study included 24 patients (8 females and 16 males) with active PR lesions, with a mean age of 28.62 years. Twenty four healthy age- and sex-matched individuals were included as controls (8 females and 16 males, with a mean age of 30.83 years). The results of the routine laboratory tests revealed no significant differences between both groups. Significantly elevated expression of all studied TLRs were detected in PR patients relative to healthy controls (p < .001). Conclusions TLRs 3, 7, 8, and 9 might be involved in the pathogenesis of PR.